2015
DOI: 10.1007/s00464-015-4126-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety and long-term outcomes of percutaneous endoscopic gastrostomy in patients with head and neck cancer

Abstract: PEG is both safe and efficacious in arresting weight loss and maintaining nutrition in patients undergoing surgery and/or chemoradiotherapy for head and neck cancer. PEG can be recommended for patients in whom dysphagia and weight loss is anticipated or in whom weight loss occurs as a result of their treatment; 20% of patients will need the PEG for a year or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…The prophylactic endoscopic gastrostomy (PEG) tube is associated with risk of complications in the short‐term, such as local infection, the formation of granulation tissue around the stoma, and a low risk of peritonitis. There is, however, a great deal of variability in the reported incidence of these complications . More recently, several studies have reported that long‐term dysphagia may be associated with the use of a PEG tube .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prophylactic endoscopic gastrostomy (PEG) tube is associated with risk of complications in the short‐term, such as local infection, the formation of granulation tissue around the stoma, and a low risk of peritonitis. There is, however, a great deal of variability in the reported incidence of these complications . More recently, several studies have reported that long‐term dysphagia may be associated with the use of a PEG tube .…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, a great deal of variability in the reported incidence of these complications. 7,8 More recently, several studies have reported that long-term dysphagia may be associated with the use of a PEG tube. 4,[9][10][11] The authors hypothesized that, when compared with NGT, a PEG tube may cause a more pronounced atrophy of the muscles responsible for swallowing because of a prolonged absence of oral intake.…”
Section: Introductionmentioning
confidence: 99%
“…In the eight retrospective series based around an index case of seeding, seeding was observed in 15 of 1742 patients with head and neck cancer (0.86%). In contrast, only two cases were identified in the randomized trial and the remaining prospective and retrospective series (2/3049; 0.07%). Combining both sets of data, the overall incidence of seeding in patients with head and neck cancer was 0.35% (17/4791) and 0.25% (1/397) in those with oesophageal cancer.…”
Section: Resultsmentioning
confidence: 94%
“…Data from the randomized trial, the 27 retrospective and 2 prospective case series are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Schurink et al (20) reported wound site infection and bleeding in 18.7% and 3% of their patients undergoing PEG, respectively. The reported 30-day mortality after PEG exhibits a wide variability between 0% and 28% (7,23,24). The discrepancy between reported rates of mortality may be related to a number of factors such as the type of neurologic disorder involved, the presence of weight loss exceeding 10% of the bodyweight, and a forced vital capacity of less than 65% in respiratory function tests (7,24).…”
Section: Discussionmentioning
confidence: 99%